Một số yêu cầu của thư viện trong kiểm định chất lượng giáo dục đại học - Trần, Dương (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
The quality of information and library activities in universities is one of the standards which is hightlighted in the set of standards for accreditation of education’s quality. The library's requirement for accreditation of education’s quality is the basis for providing information resources to meet the demand of the training and scientific research work of University education. The paper clarifies the library's standard requirements for University education accreditation.